THERMAL DISPERSION MODEL OF WATER COOLING PLTGU CILEGON CCPP DISCHARGE INTO MARGASARI COASTAL WATERS AT THE WESTERN COAST OF BANTEN BAY - I Wayan Nurjaya; Heron Surbakti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
Thermal dispersion model based on the hydrodynamics model was applied on PLTGU Cilegon (electric power industry based on gas and steam) at the coast of Margasari, Pulo Ampel District, Serang-Banten. This PLTGU used around 60.000 mP3P/hour of seawater as cooling water system. Therefore, it produced water with high temperature of about 5 PoPC higher than the sourounding of seawater temperature. This high water temperature was flowed out into the coastal waters. This study tried to predict their distribution according to southeast and northeast monsoon. Model verification was conducted both to hydrodynamics component (tide and current) and water temperature. The verification results show good enough patterns between the model results and field measurement.Key words: Bay of Banten, cooling water system, thermal dispersion, hydrodynamics model